Symmetry Breaking of Electronic Structure upon the π→π* Excitation in Anthranilic Acid Homodimer - Marcin Andrzejak; Joanna Zams; Jakub Goclon; Przemysław Kolek (Molecules)
The main purpose of this study is to characterize the nature of the low-energy singlet excited states of the anthranilic acid homodimer (AA2) and their changes (symmetry breaking) caused by deformation of the centrosymmetric, ground state structure of AA2 towards the geometry of the S1 state. We employ both the correlated ab initio methods (approximate Coupled Clusters Singles and Doubles—CC2 and CASSCF/NEVPT2) as well as the DFT/TDDFT calculations with two exchange–correlation functionals, i.e., B3LYP and CAM-B3LYP. The composition of the wavefunctions is investigated using the one-electron transition density matrix and difference density maps. We demonstrate that in the case of AA2, small asymmetric distortions of geometry bring about unproportionally large changes in the excited state wavefunctions. We further provide comprehensive characterization of the AA2 electronic structure, showing that the excitation is nearly completely localized on one of the monomers, which stands in agreement with the experimental evidence. The excitation increases the π-electronic coupling of the substituents and the aromatic ring, but only in the excited monomer, while the changes in the electronic structure of the unexcited monomer are negligible (after geometry relaxation). The increased electronic density strengthens both intra- and intermolecular hydrogen bonds formed by the carbonyl oxygen atom of the excited monomer, making them significantly stronger than in the ground state. Although the overall pattern of changes remains qualitatively consistent across all methods employed, CC2 predicts more pronounced excitation-induced modifications of the electronic structure compared to the more routinely used TDDFT approach. The most important deficiency of the B3LYP functional in the present context is locating two charge-transfer states at erroneously low energies, in close proximity of the S1 and S2 states. The range-corrected CAM-B3LYP exchange–correlation functional gives a considerably improved description of the CT states at the price of overshot excitation energies.